PENGETAHUAN, SIKAP, DAN PRAKTEK GIZI IBU TERKAIT IODIUM DAN PEMILIHAN JENIS GARAM RUMAH TANGGA DI WILAYAH PEGUNUNGAN CIANJUR - Amalia, Leily; Permatasari, Inke Indah; Khomsan, Ali; Riyadi, Hadi; Herawati, Tin; Nurdiani, Reisi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2015)
ABSTRACTThis study was aimed to analyze levels of knowledge, attitude, and practice on nutrition related to iodine, and iodine source consumption pattern, and household’s usage of iodized salt among mothers in mountainous area of Cianjur District. Design of this study was a cross-sectional, conducted during May-July 2012 at three sub-districts of Cianjur which were categorized as IDD (Iodine Deficiency Disorders) endemic areas. The subjects were 153 household mothers, living in the study area. The data were collected by interview using pre-tested questionnaires. Data on iodine content of salt was analyzed at Laboratory of Balai GAKI, Magelang. The result shows that subjects were mostly categorized as poor (73.2%), namely their income/cap/month was lower than poverty line of rural West Java. Nutritional knowledge related to iodine of subjects was categorized as moderate (score 64.2). Nutritional attitude related to iodine of subjects indicated the negative attitude (score <75), and the nutritional practice was categorized as poor (score 58.3). Type of iodine food source which frequently consumed by households were salted fish and egg. The salt consumed by households was wholely iodized salt, but only 11.1% of them complied with the iodized salt standard (>30 ppm).Keywords: attitude, iodine, knowledge, practiceABSTRAKPenelitian ini bertujuan menganalisis tingkat pengetahuan, sikap, dan praktek gizi ibu terkait iodium, serta pola konsumsi pangan sumber iodium dan penggunaan garam beriodium pada ibu rumahtangga di wilayah pegunungan Cianjur. Desain penelitian ini merupakan cross sectional, dilakukan pada bulan Mei-Juli 2012 di tiga kecamatan yang tergolong endemik GAKI (Gangguan Akibat Kekurangan Iodium) di Kabupaten Cianjur. Subjek adalah ibu rumahtangga sebanyak 153 orang. Data dikumpulkan dengan metode wawancara menggunakan kuesioner yang telah diujicobakan sebelumnya. Data kandungan iodium pada garam diperoleh berdasarkan analisis di laboratorium Balai GAKI, Magelang. Hasil penelitian menunjukkan subjek umumnya tergolong miskin (73,2%) karena pendapatan/kapita/bulan lebih rendah dari Garis Kemiskinan Jawa Barat untuk wilayah perdesaan. Pengetahuan gizi ibu terkait iodium tergolong sedang (skor 64,2). Sikap gizi ibu terkait iodium menunjukkan sikap yang negatif (skor <75) dan praktek gizi ibu terkait iodium tergolong rendah (skor 58,3). Jenis pangan sumber iodium yang sering dikonsumsi subjek adalah ikan asin dan telur. Garam yang dikonsumsi subjek semuanya sudah mengandung iodium, tetapi hanya 11,1% yang mengandung iodium dalam jumlah mencukupi (>30 ppm).Kata kunci: iodium, pengetahuan, praktek, sikap